Identifying community physical activity and health resources for treatment of back pain by utilizing members of a physical activity network - Sedney, Cara L. (BMC Public Health, 2020)
BACKGROUND: Back pain is one of the leading causes of health care expenditure in the US and is linked to an increased body mass index. Many evidence-based modalities for the prevention and treatment of back pain closely mirror recommendations for weight loss and include physical activity and health maintenance activities (PAHM). The primary aim of this study was to ascertain community assets, and perceptions of the use of PAHM in the treatment of back pain by West Virginia Physical Activity Network (WVPAN) members. METHODS: Participants for the study were recruited from the West Virginia Physical Activity Network. This grassroots organization is filled with volunteers from various sectors who were recruited from various workshops, conferences, or coalition meetings over a period of several years. This network was purposely selected as the study population because of the statewide reach and their familiarity with resources in their local communities. A brief survey instrument was designed to gather their scaled perceptions about various treatment modalities related to back pain, and to gather their local knowledge related to specific providers in their communities. In addition, participants were given a free text box to list any local assets or resources for the nine treatments listed, and county of residence, and the nature of their connection to the physical activity network. Descriptive analyses were used to describe overall patterns of survey data. The qualitative data were compiled manually by the research team to show themes of specific treatments mentioned across different parts of the state. RESULTS: Participants overwhelmingly supported physical therapy, flexibility training, yoga, and core strengthening as treatments for back pain. The majority of respondents were “undecided” about other treatments such as cognitive behavioral therapies and acupuncture. CONCLUSIONS: The implementation of PAHM interventions in communities could help treat patients with back pain, and may reduce reliance on the pharmacological treatment for back pain. The current study’s data support the potential of such approaches in many West Virginia counties. Also, local resources, and context can be gleaned from community leader surveys utilizing previously developed infrastructure for PAHM promotion.